Did Recent Tobacco Reforms Change the Cigarette Market?. Issue 1 (6th December 2017) - Davidson, Sinclair; de Silva, Ashton
Abstract : The Australian tobacco market is very tightly regulated. Australian governments, like many others, have a long history of enacting various forms of control, including restricting advertising and imposing taxes. Using Australian government data, we investigate the effects of controls on cigarette market characteristics coinciding with Australia's introduction of plain packaging in 2012 (arguably the most innovative form of tobacco control in many years) as well as a subsequent tax increase. Using these data, we find no evidence to suggest that prices and market shares, key market characteristics, changed as a result of plain packaging. Moreover, using a second data set, we find that the introduction of plain packaging had no discernible effect on smoking rates. This finding is not surprising as both domestic and international research shows that government attempts to discourage new consumers, and encourage current consumers to quit, have not been very successful.